Cloning, expression and characterization of recombinant CagA protein of Helicobacter pylori using monoclonal antibodies: Its potential in diagnostics. (November 2020) - Salih, Barik A.; Karakus, Cebrail; Ulupinar, Zeynep; Akbas, Fahri; Uslu, Merve; Yazici, Duygu; Bolek, Bora Kazim; Bayyurt, Nizamettin; Turkay, Cansel
Abstract: Helicobacter pylori CagA protein plays an important role in the severity of the gastric diseases. Our aims were to clone the cagA 5′- conserved region of the gene, characterize the recombinant CagA (rCagA) protein by monoclonal antibodies (mAbs) and to use this protein for the detection of anti-CagA antibodies by an ELISA test. Our developed rCagA protein (67 kDa) showed an amino acid sequence homology of 83% and 80% with Western and East Asian type strains respectively. Two anti-rCagA (BS-53, CK-02) mAbs and 2 additional rCagA proteins of smaller sizes (60 kDa, 28 kDa) were developed for epitope determination. The BS-53 mAb recognized all 3 rCagA proteins while CK-02 mAb recognized only 2 of them indicating recognition of different epitopes. An in-house indirect ELISA using rCagA was developed to detect anti-CagA antibodies in sera of 59 patients. The ELISA results obtained when compared to those of the PCR gave a sensitivity, specificity and accuracy of 81%, 100% and 88% respectively. We have developed for the first time: a rCagA protein that showed high sequence homology with both Western and East Asian type strains and an indirect ELISA of high performance which can be used to detect anti-CagA antibodies in sera of infected patients worldwide.